Efficacy of whole cell vaccine Aeromonas hydrophila on catfish broodstock and it’s offspring resistance againt motile aeromonad septicemia (MAS) - Sukenda, ,; Pratiwi, Kiki Amalia; Rahman, ,; Hidayatullah, Dendi (Indonesian Society of Scientific Aquaculture (ISSA), 2017)
ABSTRACT Transfer of maternal immunity by mean of passive immunization is a way to provide protection and durability of antibodies on the offspring. The purpose of this research was to analize effication of Aeromonas hydrophila vaccine on the catfish broodstock to maternal transfer of immunity, and offspring resistance. The average body weight of broodstock used in this study were 650±50 g were kept in pool tarps sized 2×1×0.5 m3. This study used a randomized complete design with two treatments and three replications. Female broodstock were vaccinated using intraperitonial injections at a dose 0.4 mL/kg and control fish were injected with phospate buffered saline (PBS). The observed parameters include hematology of broodstock, mortality, the relative survival rate, and antibody titers. Antibody titer measurements on broodstock, eggs, and offspring. Vaccination on broodstock catfish delivers a significant antibody level (P<0.05) on offspring compared to control catfish with relative survival rate of offspring at 5, 10, and 15 days after hatching were 67.76%, 82.66%, and 71.66% respectively. Keywords: catfish, Aeromonas hydrophila, vaccination, antibody transfer ABSTRAK Transfer kekebalan dari induk kepada benih melalui imunisasi pasif merupakan salah satu cara untuk memberikan proteksi pada benih. Tujuan penelitian ini untuk menguji efikasi vaksin sel utuh Aeromonas hydrophila pada induk ikan nila dalam mentransfer kekebalan spesifik ke benih dan menguji ketahanan benih hasil pemijahan induk yang divaksin. Induk lele yang digunakan pada penelitian ini memiliki bobot rata-rata 650±50 g dipelihara di kolam terpal berukuran 2×1×0,5 m3. Penelitian ini menggunakan rancangan acak lengkap dengan dua perlakuan dan tiga ulangan. Induk betina lele divaksinasi secara intraperitonial dengan dosis 0,4 mL/kg ikan dan induk lele kontrol disuntik dengan phospate buffer saline (PBS). Parameter yang diamati meliputi hematologi induk, mortalitas, tingkat kelangsungan hidup relatif benih, dan titer antibodi. Vaksinasi induk lele memberikan hasil level antibodi yang signifikan (P<0,05) pada induk, telur, dan benih lele dibandingkan perlakuan kontrol dengan tingkat kelangsungan hidup relatif benih umur 5, 10, dan 15 hari pacatetas masing-masing sebesar 67,76; 82,66%; dan 71,66%. Kata kunci: ikan lele, Aeromonas hydrophila, vaksinasi, transfer antibodi